2011
DOI: 10.5713/ajas.2011.10068
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Caponization on Muscle Composition, Shear Value, ATP Related Compounds and Taste Appraisal in Taiwan Country Chicken Cockerels

Abstract: An experiment was conducted to determine the effects of caponization on the muscle composition, ATP-related compounds, the shear values, the taste panel scores and the muscle fiber areas of Taiwan country chicken cockerels. At 10 wks of age, cockerels were divided into two groups: caponized and untreated. Birds were fed grower and finisher diets ad libitum in an eighteen-week experimental period. Results showed that capons contained significantly greater muscle fat content, less breast and thigh muscle moistur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…According to Lyon and Lyon (1991) meat with shear force values <3.62 kg/cm 2 is very tender meat, confirming that samples of the present study can be considered very tender, highlighting the Pedrês breed. Breast moisture (72% to 73%) and protein content (23% to 24%) are within the range values reported by several authors, in cock and capon of Castellana Negra (Miguel et al, 2008), in hybrid broiler (Sirri et al, 2009) and Taiwan country chickens (Lin et al, 2011). Breast meat capon showed greater CP content and IMF, in comparison with roosters, but no differences were found for moisture, myoglobin, ash and collagen contents in contradiction with Miguel et al (2008), Sirri et al (2009) and Volk et al (2011) that have reported that caponisation had no effect on moisture and CP contents.…”
Section: Meat Physical and Chemical Characteristicssupporting
confidence: 88%
See 4 more Smart Citations
“…According to Lyon and Lyon (1991) meat with shear force values <3.62 kg/cm 2 is very tender meat, confirming that samples of the present study can be considered very tender, highlighting the Pedrês breed. Breast moisture (72% to 73%) and protein content (23% to 24%) are within the range values reported by several authors, in cock and capon of Castellana Negra (Miguel et al, 2008), in hybrid broiler (Sirri et al, 2009) and Taiwan country chickens (Lin et al, 2011). Breast meat capon showed greater CP content and IMF, in comparison with roosters, but no differences were found for moisture, myoglobin, ash and collagen contents in contradiction with Miguel et al (2008), Sirri et al (2009) and Volk et al (2011) that have reported that caponisation had no effect on moisture and CP contents.…”
Section: Meat Physical and Chemical Characteristicssupporting
confidence: 88%
“…There were no sex differences for texture, confirming the results obtained by Symeon et al (2010) and Calik et al (2015) in capons with 18 and 24 weeks of age, respectively. However, Sirri et al (2009), Symeon et al (2010 and Lin et al (2011), observed that caponisation decreases texture values in capons with 180 days, 24 and 28 weeks of age, respectively. Breed differences were found and the Amarela had tougher meat than Pedrês.…”
Section: Meat Physical and Chemical Characteristicsmentioning
confidence: 96%
See 3 more Smart Citations